Tuvans’ Views on Children: Changes of the Attitudes in Socio-cultural Transformations - Lamazhaa, Chimiza K. (The New Research of Tuva, 2021)
The article analyzes the issue of the transformation of adults’ attitude to children in Tuvan society amid general social changes in the 20th and 21st centuries. The historical and cultural research was carried out with the use of methods of social and cultural anthropology. The attitude towards children is considered as part of the culture of childhood, a children’s subculture. The relevance of the study is due to the overt crisis of modern parenting among the Tuvans.In the traditional Tuvan society, the culture of childhood was developing under conditions provided by the society with the clan system of living. Children were the focus of attention, they were given every care and support. The tribal community guaranteed their protection. This traditional model was formed throughout the entire cultural genesis. It allowed, among other things, the development of sentiments towards children — praising, fascination, admiration, and affection.In Soviet times, children ceased to be only the object of parental care. Parents were controlled by the tribal community. As in all corners of the Soviet country, children became the objects of state policy. The influence of parents and especially of a wide range of relatives was reduced and even pushed aside in particular by the education and upbringing system. The teaching and educational program was based on a general policy. Parenthood itself ceased to be as important for the culture of childhood as it used to be. Children became a public resource and an unknown “variable” for parents in terms of a future for their family.In the post-Soviet period, the state has lost its superiority as a regulator. Westernization trends and technological innovations that have appeared in the course of globalization are now new factors that determine the features of the culture of childhood. In these conditions, new additional motives in the attitude of adults towards children have emerged — they are common and devoid of the Tuvan ethnic constituent. The increased period of infantilism of the youth and young parents leads to irresponsibility towards children, the desire to live on child benefits and maternity capital. Another form of Tuvan parents’ attitude to children is hyperprotection and hypercare. A significant part of the Tuvans have made it the norm to provide the child with everything necessary not only in childhood, but also in subsequent adulthood.
Keywords: Tuvans; kinship; children; culture of childhood